A middle Cambrian (Series 3, Stage 5) microfaunal assemblage from the Torgau-Doberlug Syncline (Central Germany) and its palaeogeographic implications for the configuration of West Gondwana - Atnisha, Abubaker (Acta Geologica Polonica, 2019)
A microfauna of small shelly fossils (SSF) is reported here for the first time from middle Cambrian (Series 3, Stage 5) subsurface strata of the Torgau-Doberlug Syncline (TDS), Central Germany. Considering that this microfauna is strongly limited and poorly preserved the material is quite abundant and diverse. The assemblage consists of molluscs (pelagiellids, bivalves), coeloscleritophorans (chancelloriids, halkieriids), poriferids, protoconodonts, cambroclaves, hyoliths, brachiopods, and disarticulated echinoderm remains. Additionally, a probable pterobranch hemichordate is noted. The assemblage is dominated by epifaunal suspension feeders from mid- to outer shelf depositional settings. Stratigraphically it represents (together with rare trilobites) the oldest middle Cambrian (Series 3, Stage 5) fauna known from Central Germany and the entire Saxothuringian Zone. Regardless the taphonomic problems related to the SSF occurrence, close palaeobiogeographic relations are indicated with the Mediterranean shelf of West Gondwana (especially with the areas of southwestern Europe and Morocco). The reported microfauna coupled with recent trilobite and palynomorph research supports assumptions that the Cambrian succession in the TDS is by far more complete than hitherto suggested, emphasizing its importance as a region yielding Cambrian rocks in Central Europe.
Keywords: Small shelly fossils; Cambrian; Torgau-Doberlug Syncline; Germany; West Gondwana